SISTEMA MULTIAGENTE PARA AVALIAÇÃO DO EFEITO DE AGLOMERAÇÃO EM NANOPARTÍCULAS POLIMÉRICAS - Zamberlan, Alexandre de Oliveira (2018)
Production and characterization of polymer nanoparticles (PNPs), colloidal dispersions, are processes that require time and technical skills to produce accurate results. Computational simulations in Nanoscience have aided in these processes, providing support and agility to achieve better results. In this work, the challenge was to show, previously, by computational simulation, the agglomeration behavior, which indicates instability in a nanoparticulate system. These PNPs are used for transport and delivery of drugs in various treatments. The Computing area has methods based on behaviors derived from nature, such as systems of intelligent collective behavior or MAS. Such systems are composed of agents - programs - living in society, which interact with each other. This approach facilitates the implementation of real systems that require observation of specific behavior, since each agent can be programmed individually to perceive other agents, the environment and respond to these perceptions so that the behavior of the system arises from the interactions of these agents agents. Thus, the objective of the work was to evaluate the agglomeration effect of polymer nanoparticles (PNPs) through design, implementation and testing of the simulation environment using MAS theory. The methodology used was computer simulation supported by a case study. For the case study, a simulation environment was constructed with functionalities to produce interactions between particles from physical-chemical parameters, that guarantee the Brownian movement with elastic and inelastic collisions. This environment, named "Multi-Agent System for Polymeric Nanoparticles" (MASPN), has been developed according to the Feature Driven Development (FDD) methodology of software design and the methodology of Multi-Agent Systems. In addition, we used the event-oriented simulation package algs4 and the JASON agent building environment, all integrated by Java technology. The package has implementations of various functions for scientific computing and event-oriented simulation, including resolution of particle-particle and particle-wall collisions, obeying the stochastic model of Brownian motion. The MASPN environment emerges as the main result of this research, since it is an alternative simulation tool, containing graphical interface with integrated physicochemical parameters, distribution graphs (particle size, particle zeta potential and environment pH), particle animation under the Brownian mathematical model.The parameters of the simulations, for evaluation of the agglomeration effect, are size, size distribution, surface electric charge, mass, drug content and pH. Finally, the simulation environment designed and built, integrating areas, methodologies and technologies, can be considered a resource in the production and characterization of polymer nanoparticles, since the simulations performed had significantly accurate results. In addition, we can be stated that scientifically this research provides perspectives of future work in Pharmacy, Chemistry, Physics and/or Computing.